THE SUSTAINABILITY OF FLORA, FAUNA AND GEOMETRIC MOTIF DESIGNS AMONG BATIK TULIS MANUFACTURERS IN KLANG VALLEY - Ahmad Hakim Abdullah; Mohd Azhar Samin, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The purpose of this research is to find out the development of the batik tulis industry in the Klang Valley from the 1970s until 2018. It aims to study the design and identity of the batik tulis motif and patterns. This research used several methods and approaches for data collection which consisted of interviews, observations, and photo documentation. Three batik tulis manufacturers in the Klang Valley have been selected for this study. The data collected were then analysed using an analytical design approach. The findings showed that each manufacturer of batik tulis has exclusivity in terms of its subject matter as well as assertions in the patterns and designs used. The development of the batik tulis industry has changed in terms of designs according to the demands of batik consumers themselves who prefer differentiation in the design concept of batik products. Most of the batik products in the Klang valley are more focused on the concept of modern and contemporary designs for the sustainability of these batik motif design.